2020
DOI: 10.1002/bjs.11393
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to minimize intraoperative blood loss during major surgery

Abstract: Background Reducing operative blood loss improves patient outcomes and reduces healthcare costs. The aim of this article was to review current surgical, anaesthetic and haemostatic intraoperative blood conservation strategies. Methods This narrative review was based on a literature search of relevant databases up to 31 July 2019 for publications relevant to reducing blood loss in the surgical patient. Results Interventions can begin early in the preoperative phase through identification of patients at high ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 133 publications
(129 reference statements)
1
57
0
1
Order By: Relevance
“…Permissive hypotension refers to the lowering of mean arterial pressure to values between 50 and 65 mm Hg with the goal of reducing blood flow to the surgical field, thereby reducing blood loss and improving visibility in the surgical field. 50 Studies have shown that permissive hypotension during anaesthesia reduced blood loss in spinal surgery, radical prostatectomy, functional endoscopic sinus surgery, and orthopaedic surgery. [51][52][53] It can also reduce blood loss and blood product utilisation in adult trauma patients with haemorrhagic shock.…”
Section: Minimising Blood Lossmentioning
confidence: 99%
“…Permissive hypotension refers to the lowering of mean arterial pressure to values between 50 and 65 mm Hg with the goal of reducing blood flow to the surgical field, thereby reducing blood loss and improving visibility in the surgical field. 50 Studies have shown that permissive hypotension during anaesthesia reduced blood loss in spinal surgery, radical prostatectomy, functional endoscopic sinus surgery, and orthopaedic surgery. [51][52][53] It can also reduce blood loss and blood product utilisation in adult trauma patients with haemorrhagic shock.…”
Section: Minimising Blood Lossmentioning
confidence: 99%
“…These clinical characteristics will affect the blood loss and hemostasis of patients and the changes of their vital signs during surgery, the length of time in surgery, and the size of the surgical wounds, but cannot predict accidents that may occur during surgery. These clinical features must be observed preoperatively, but not during or after surgery [5][6][7] . Moreover, the in uencing factors for different diseases may vary, so this scoring system is different from other preoperative scoring systems, such as the system proposed by the American Society of Anesthesiologists 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Blood loss during any type of surgery is one of the biggest problems faced in the OR today. Out of the estimated 313 million surgical procedures that are done worldwide annually, recent estimates show that at least 4.2 million people die within the 30 days of surgery per annum, which accounts for 7.7% of all deaths [1]. Perioperative bleeding remains a major risk during and after surgery and is associated with a high rate of death, complications, and healthcare resource use.…”
Section: Introductionmentioning
confidence: 99%